Evaluasi Penetapan Kota Terpadu Mandiri (KTM) di Kabupaten Sarolangun - , Herning Ratna Kusumawati, SE ([Yogyakarta] : Universitas Gadjah Mada, 2011)
The objective of this research is, firstly, to understand the analysis of typology of district area or a city to held autonomous integrated city (KTM) immediately. The second is to understand the criteria and types of major commodity which can be developed as economic motivator in the area and investation need. The third is to understand how to formulate a strategy to held autonomous integrated city immediately in Sarolangun, Jambi. This explorative study is to formulate a guidelines concept of development and the growth (strategy and program) of KTM as the center of the growth. The location used in this research was KTM of Pauh Mandiangin, Sarolangun, Jambi. The collecting data method used two methods, secondary and supporting data. The collecting data used secondary data, e.g. PDRB District and Province of Jambi for 3 years. To analyze the potential of the area, this research used Location Quotient (LQ). The comparison of domination Index of inter sub-region and grouped region is known as SLQ. Besides using SLQ to analyze sector which was potential to improve the economic growth in certain area, it also used Dynamic Location Quotient analysis (DLQ). The typology of area is an analysis classifying area into 4 classifications. There are area which is quickly to grow and to be a developed area, area which is faster to develop, area which is developed but under pressure, and area which is left behind (a lagging area). Sarolangun is a lagging area as the result of SLQ and DLQ. From 9 sectors of Sarolangun, these were agricultures, veterinary, plantation, fishery and construction sectors which were still being the major sectors. The important aspects used as consideration to accelerate the KTM development in Sarolangun are 1) primary commodity as development basic of KTM is agriculture and plantation, crop and holticulture sectors